The Relationship between Homework and Motivation for Learning among Arab Elementary School Students in Israel - Atamna, Jamila (Rocznik Pedagogiczny, 2021)
Students, parents, teachers and researchers in the field of education disagree with each other about the contribution of homework in the overall student learning process. In particular, widespread criti- cism is directed at the emotional and cognitive load that homework imposes on the student, the con- siderable time they consume, and the disruption caused, according to the claim, to the social devel- opment of the student. This claim is supported by a series of empirical studies that have been carried out for decades, especially recently, in the world and in Israel. Nevertheless, the role that homework plays in the student learning process and their impact on other components of the student’s learning experience has never been studied in Arabic-speaking schools in the country.